Revealing nanoscale lithiation and dissolution pathways by in situ cryogenic electron microscopy - Tiukalova, Elizaveta (Nanyang Technological University, 2022)
Materials for energy storage and conversion devices are of high importance to meet future industrial energy demands. Detailed understanding of chemical processes occurring at the solid/liquid interfaces and alterations of the structure at the atomic scale is critical for the design and development of future devices. This Ph.D. work focuses on two central systems of particular relevance for energy applications, i.e., LiNi0.5Mn1.5O4 Li ion battery cathode material and two catalysts (La2LiIrO6, ZnCo1.2Ni0.8O4) for the oxygen evolution reaction (OER) applications. Through a deep understanding of the evolution of the structure at the local atomic scale, the overall aim is to get insights into the atomic structure property relationship to improve our understanding and provide information that will help develop materials capable of higher capacity, longer lifetime, and overall better performance.